Connecting AI and SEL: A New Approach in Teacher Education (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
The study addresses the critical need for artificial intelligence (AI) literacy in teacher education and explores the most effective methods of equipping teachers in this emerging field, suggesting that a combination of AI literacy and Social-Emotional Learning (SEL) could substantially boost digital proficiency beyond conventional training approaches. The research employs quantitative analysis, initially surveying 571 pre-service and in-service teachers, and following up with 252 participants after a 12-hour course. The study utilized various self-reporting and standardized instruments to assess the programme's effectiveness. Notably, the effect size for self-reported competence in AI integration within teaching practices was found to surpass Hattie's hinge point twice, underlining its substantial impact on educational outcomes. Other measures, though slightly less striking, also achieved increases in digital competences surpassing other similar studies. This highlights the potential of combining AI literacy with SEL in teacher education to elevate digital competence effectively.